Overnight supplemental low red light improves lettuce growth - Medelo, Maria José Yañez [UNESP]; Cecílio Filho, Arthur Bernardes [UNESP]; Carvalho, Rogério Falleiros [UNESP]; Nascimento, Camila Seno [UNESP]; dos Reis Cardoso Passos, Danilo [UNESP] (Springer Nature, 2023)
Hydroponic cultivation of lettuce in south-eastern Brazil is carried out under short days (about 10.5 to 12 h of light). Although the positive effect of light supplementation on lettuce is recognised, the effect of low irradiance of red light on the plant is not known, which may be relevant in the economic aspect and assist in the diffusion and adoption of the technology. Here, we tested the increase of light absorption efficiency when mulch is applied on hydroponic benches. The presence of mulch (restricted to hydroponic channels and over the entire bench) and red light irradiances (0, 0.8, 1.6 and 2.4 μmol m−2 s−1) were evaluated on lettuce growth. No effects of growing season were observed on the biometric characteristics evaluated. Overnight supplementation with low red light acted positively in both autumn and winter, promoting an increase in plant growth and, consequently, yield. Mulching over the entire bench does not contribute to greater reflectance of red light applied to plants compared to mulching restricted to the channels.
Keywords: Artificial light; Hydroponic cultivation; Lactuca sativa; Protected cultivation; Urban farm